Knit two - Jacobs, Kate, 1973- (Jacobs, Kate, 1973- Friday Night Knitting Club novel., 2008)
Knit Two returns to the Manhattan knitting store Walker & Daughter five years after the death of the store's owner, Georgia Walker. Georgia's daughter Dakota runs the knitting store part-time with the help of the members of the Friday Night Knitting Club. Drawn together by their love for Dakota and the sense of family the club provides, each knitter is struggling with new challenges.